EFEKTIFITAS BUBUK ARANG TEMPURUNG KELAPA TERHADAP PENURUNAN KADAR WARNA, BAU DAN RASA AIR GAMBUT DESA KUALU KECAMATAN TAMBANG - Desi Hidayanti Muas; Sukendi Sukendi; Sofia Anita (Program Pascasarjana Universitas Riau, 2019)
Water is a natural resource that has a renewable potential because the availability of water in nature follows a cycle that involves various ecosystem components. The purpose of this study was to analyze the color, odor and taste of peat water before and after treatment by applying coconut shell charcoal powder and determine the optimal weight of coconut shell charcoal powder which is effective against decreasing the color, odor and taste of peat water. The research population is the peat water area located in Kualu Village, Tambang District, Kampar Regency. The data analysis technique of this study used Analysis of Varianse (ANOVA). The results of this study are (1) Conditions of the levels of color, odor and taste in peat water before treatment with coconut shell charcoal powder, where in the tests carried out in looping 1 to looping 5 have the same results (consistent), namely the results of the color of 86.21, from the odor results stated (Smelled ++++), and the results of the taste stated (Asam ++++), (2) There was a significant / significant difference between the color, odor and taste of peat water before and after contacting with coconut shell charcoal adsorbent (weight variation) and (3) Optimal weight of coconut shell charcoal powder which is effective in reducing the color, odor and taste of peat water in the StD sample group: After contacting (50 g / 1L).